PENDIDIKAN DAN PEKERJAAN IBU HAMIL TERHADAP KEIKUTSERTAAN SENAM HAMIL - Henny Juaria (Akademi Kebidanan Griya Husada Surabaya, 2018)
Pregnant gymnastics is a physical exercise in the form of certain movements carried out specifically to improve the health of pregnant women. Based on data at Jagir Surabaya Health Center from the period of January 2015 - December 2016 the number of pregnant women who participated in the pregnancy exercise program experienced a large decrease (56.58%) compared to the period January 2014 - June 2015 the number of mothers taking pregnancy exercise increased (31, 24%). Therefore this study aims to determine the relationship between education and employment of pregnant women on the participation of pregnant gymnastics. The method of this research was carried out by cross sectional analytical method. The population is all third trimester pregnant women (?28 weeks - 40 weeks) totaling 244 people and the sampling technique used was simple random sampling with a total of 71 people. Data obtained from secondary data and processed results in frequency tables, cross tabulation and tested with Chi-Square with the provisions of abel2 table 3.84 (? = 0.05). Results: The results of the study showed that mothers who had a low level of education did not take part in pregnancy exercise, namely as much as 82.35% and the majority of working mothers were not participating in pregnancy exercises, namely 77.42%. The Chi-Square test results between education and the participation of pregnant gymnastics are ?2 Calculate> ?2 Table (4.45> 3.84) and from the aspect of work obtained didapatkan2 Count> ?2 Table (6.54> 3.84). Discussion: From the results of the study it was found that there was a relationship between the level of education of the mother and the participation of pregnancy exercise and there was a relationship between the work of the mother and the participation of the pregnant gymnastics. Therefore, it is expected that health workers are able to further improve the quality of services by providing information on the importance of conducting pregnancy exercises through counseling, discussion or the provision of routine pregnancy exercises.